1979
DOI: 10.1136/jcp.32.10.1036
|View full text |Cite
|
Sign up to set email alerts
|

EB virus-specific IgA in serum of patients with infectious mononucleosis and of healthy people of different ages.

Abstract: SUMMARY The following sera were tested for EB virus-specific IgA: serial sera from 61 cases of infectious mononucleosis (IM) and from 195 EBV IgG positive healthy students; single sera from each of 1469 persons of different ages, 63 cases of untreated Hodgkin's disease, and 22 neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…http://jid.oxfordjournals.org/ Downloaded from 1970s showed 2 peaks of EBV seroconversion, one at ages 6-7 years and another at ages 14-15 years [16,17]. Although it has been suggested that the first peak of infection is due to virus spread by family members and the second due to virus spread through sexual contact, there is very limited evidence to support this supposition.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…http://jid.oxfordjournals.org/ Downloaded from 1970s showed 2 peaks of EBV seroconversion, one at ages 6-7 years and another at ages 14-15 years [16,17]. Although it has been suggested that the first peak of infection is due to virus spread by family members and the second due to virus spread through sexual contact, there is very limited evidence to support this supposition.…”
Section: Discussionmentioning
confidence: 97%
“…The 63.7% prevalence of seropositivity in students who had never had sexual intercourse is presumably largely or entirely a consequence of seroconversion in childhood. It is somewhat higher than the 45%-50% seropositivity at ages 10-12 years found in Britain in the 1970s [16,17]; perhaps childhood seroconversion has become more common over time, or some seroconversion unconnected with sexual intercourse may occur at older ages. It seems unlikely that there were appreciable numbers of students who had had sexual intercourse but replied that they had not; the replies in the questionnaires seemed to be very frank, and this is our experience of the students.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…If, as has been suggested (17), the EB virus is one of the several etiologic agents, the high prevalence of antibodies to EB VCA in adult normal sera makes the use of this feature difficult in seeking a causal relationship. One approach is to examine the sera of children, who have a much lower prevalence of EB virus antibodies (15). However, in a previous study, it has been shown that the prevalence of antibodies to EB VCA in juvenile chronic arthritis corresponds to that expected for their age (2).…”
Section: Discussionmentioning
confidence: 99%